1981
DOI: 10.1111/j.0954-6820.1981.tb02599.x
|View full text |Cite
|
Sign up to set email alerts
|

CLASSIFICATION OF CARDIOACTIVE DRUGS IN VIVO BY USING PROGRAMMED ELECTRICAL STIMULATION IN COMBINATION wITH MONOPHASIC ACTION POTENTIAL RECORDINGS AT DIFFERENT PACING RATES

Abstract: ABBREVIATIONS MDP = maximal diastolic potential, AP = action potential, Vmax = maximum rate of rise, ERP = effective refractory period, MAP = monophasic action potential, MAPD,, = time for 50% repolarization of MAP. ABSTRACTThe effect of antiarrhythmic drugs on myocardial refractoriness may be due to changes either in V, , , of phase 0 or the phase of repolarization of the AP or both. By using programmed electrical stimulation in combination with MAP recordings at different pacing rates in :he intact dog heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Studies o n isolated heart muscle preparations (Refsum et a/. 1978;Arlock et al 1978), intact dog hearts Landmark et al 1981) a n d man (Edvardsson & Olsson 1981) have suggested that melperone may be a class 111 antiarrhythmic drug according t o the classification of Vaughan Williams (1975). Based o n their study on patients with acute myocardial infarction, however, Magelvang et a/.…”
mentioning
confidence: 99%
“…Studies o n isolated heart muscle preparations (Refsum et a/. 1978;Arlock et al 1978), intact dog hearts Landmark et al 1981) a n d man (Edvardsson & Olsson 1981) have suggested that melperone may be a class 111 antiarrhythmic drug according t o the classification of Vaughan Williams (1975). Based o n their study on patients with acute myocardial infarction, however, Magelvang et a/.…”
mentioning
confidence: 99%